PENYULUHAN PERAN ASI EKSKLUSIF TERHADAP TUMBUH KEMBANG ANAK DITENGAH WANITA PEKERJA PEDAGANG PASAR TRADISIONAL - Aryani, Peny; Ariescha, Putri Ayu Yessy; Siagian, Nurul Aini; Andriani, Andriani (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Exclusive breastfeeding is giving breast milk to babies from 0-6 months of age exclusively without additional food or drink. Exclusive breastfeeding provides many benefits for both baby and mother. Some of the benefits of exclusive breastfeeding for babies are increasing the baby's body resistance or antibodies against disease attacks and helping the baby's brain and physical development. For the Deli Serdang Regency area, the percentage of babies who receive exclusive breast milk is only 47.26%. From these data it can be seen that there is still a lack of exclusive breastfeeding for babies. The low level of exclusive breastfeeding will have an impact on the quality and vitality of the next generation. One of the factors that hinders exclusive breastfeeding is working mothers, especially in the informal sector such as traditional market traders. This PKM activity using the counseling method aims to provide information to breastfeeding mothers about the role of exclusive breastfeeding in the growth and development of babies among women who work as traders at the Deli Tua traditional market. The process of implementing this community service activity is carried out by providing information and education to respondents regarding the role of exclusive breastfeeding in the growth and development of babies and tips on how to meet the needs of exclusive breastfeeding for children among women who work as traditional market traders. Then the respondents distributed pre-test and post-test questionnaires to the participants and the results obtained were 76.9% of the 13 respondents had increased knowledge regarding the role of exclusive breastfeeding in the growth and development of babies and tips on how to meet the needs of exclusive breastfeeding for children among working women. as a traditional market trader.